Radiobiological And Clinical Comparison of Single-Session Versus Hypofractionated Gamma Knife Radiosurgery for Medically Refractory Trigeminal Neuralgia - Mohammed Hassan Alewi; Siham Sabah Abdullah; Moneer Khammas Faraj; Mohammed Hassan Alewi; Siham Sabah Abdullah (Universitas Negeri Malang, 2026)
Background: Gamma Knife radiosurgery (GKRS) is a well-established treatment modality for patients with medically refractory trigeminal neuralgia (TN). Although single-fraction treatment remains the conventional standard, recent technological developments have enabled hypofractionated delivery. The biological and clinical implications of these alternative fractionation schedules remain insufficiently characterized. Objective: To compare the radiobiological, dosimetric, and clinical outcomes of single-session and hypofractionated GKRS in patients with medically refractory TN. Methods: A retrospective cohort study was performed involving 62 patients treated with GKRS between January and June 2026. Forty patients underwent conventional single-session treatment (80 Gy in one fraction), while 22 patients received hypofractionated treatment (20 Gy in four fractions). Clinical outcomes were assessed using the Barrow Neurological Institute (BNI) Pain Intensity and Facial Hypesthesia scales at baseline and during 1-, 3-, and 6-month follow-up. Biologically effective dose (BED) and equivalent dose in 2-Gy fractions (EQD2) were calculated using the linear–quadratic model. Results: Both treatment approaches resulted in significant reductions in pain severity during follow-up (p < 0.001). At six months, successful pain control (BNI ≤ IIIb) was achieved in 72.5% of the single-session cohort and 77.3% of the hypofractionated cohort (p = 0.914). Single-session GKRS generated substantially higher target BED and EQD2 values (p < 0.001), whereas hypofractionation significantly reduced brainstem BED and EQD2 (p < 0.001). Despite these radiobiological differences, no significant between-group differences were observed in pain response, complete pain relief, or treatment-related numbness. Conclusions: Hypofractionated GKRS achieved pain outcomes comparable to conventional single-session treatment while significantly decreasing radiobiological exposure to the brainstem. These findings suggest that hypofractionation may provide an effective treatment alternative with enhanced normal tissue sparing. Larger prospective studies with longer follow-up are warranted to validate these observations.